O Desenvolvimento da ciência segundo Thomas S. Kuhn : análise e crítica do modelo proposto na estrutura das revoluções científicas - Ramalho, Vagner Gomes (2014)
Thomas S. Kuhn´s book, The Structure of Scientific Revolutions (1962), was received by the philosophical and scientific community as a revolutionary text. In it, Kuhn proposed a new way of comprehending scientific development. Unlike other philosophers of science of his day, who saw scientific development as a long, accumulative process, Kuhn proposed that scientific development is marked by disruptive processes called |scientific revolutions|. With the release of the Japanese edition of Structure, in 1969, Kuhn introduced an Afterword, which I consider to be an integral part of his concept of scientific development, as it´s complementary to his model and clarifies issues addressed in the 1962 work. According to the initial development model proposed in this Structure/Afterword set, disruptions in the scientific development process are marked by a succession of paradigms. These paradigms, for Kuhn, are a type of theoretical-methodological framework. They direct scientific activity towards the comprehension of phenomena studied by a scientific community. With this Dissertation I intend to critically analyse the scientific development model proposed in Structure, discussing the key concepts necessary for understanding this model.